Existences of Mean Square Convergence for RL Circuit using Random Fourth Order Runge Kutta Method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a random stochastic initial value problem for a RL circuit is considered and the mean square convergent is proved through the random Runge Kutta method and its expectation and variance are computed.